Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/apt.15409
|View full text |Cite
|
Sign up to set email alerts
|

Gastric MALT lymphoma in a population‐based study in France: clinical features, treatments and survival

Abstract: Summary Background Gastric mucosa‐associated lymphoid tissue (MALT) lymphoma is a rare disease, and most available data on gastric MALT lymphoma (GML) come from clinical studies of selected patients treated in centres of excellence. Aims To analyse the clinical features, management and survival of GML patients in a population‐based study in France Methods All new cases of GML diagnosed between 2002 and 2010 in 11 French areas covered by cancer registries were included. Pathology reports were verified and, if n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 57 publications
(182 reference statements)
2
35
1
Order By: Relevance
“…Related reports indicated that it is frequently diagnosed as an advanced tumour, and misdiagnosis and excessive treatment can occur. [ 13 ] Common endoscopic manifestations of gastric MALT lymphoma include ulcers (45%), intragastric nodules (30%) and pseudogastritis (25%). [ 14 ] The endoscopic findings of a diffuse miliary appearance of gastric mucosa, with slightly white and small protrusions, were reported in 2 cases, and nodular gastric MALT lymphoma was considered and pathologically confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Related reports indicated that it is frequently diagnosed as an advanced tumour, and misdiagnosis and excessive treatment can occur. [ 13 ] Common endoscopic manifestations of gastric MALT lymphoma include ulcers (45%), intragastric nodules (30%) and pseudogastritis (25%). [ 14 ] The endoscopic findings of a diffuse miliary appearance of gastric mucosa, with slightly white and small protrusions, were reported in 2 cases, and nodular gastric MALT lymphoma was considered and pathologically confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…24 In a retrospective study of >400 cases diagnosed in France between 2002 and 2010, only 57% of the cases were associated with H. pylori. 25 Another point is that the density and detectability of H. pylori have been reported to decrease in association with lymphoma progression. 26,27 In intestinal MALT lymphomas, an association with Campylobacter jejuni infection has been reported, but evidence for a causal link is lacking.…”
Section: A L T L Y M P H O M Amentioning
confidence: 99%
“…However, recent analyses have shown a significant reduction in the prevalence of H. pylori infection in gastric MALT lymphomas in Europe as compared with the early 1990s 24 . In a retrospective study of >400 cases diagnosed in France between 2002 and 2010, only 57% of the cases were associated with H. pylori 25 . Another point is that the density and detectability of H. pylori have been reported to decrease in association with lymphoma progression 26,27 .…”
Section: Small B‐cell Lymphomasmentioning
confidence: 99%
“…The prognosis of primary GML patients can be affected by many factors. Clinical risk factors, including age, type of therapy, sex, stage and family hematologic malignancy history, also have signi cant effects on the development of the disease [11][12][13][14]. Meanwhile, previous studies demonstrated a good prognosis of the disease, with 5-year survival rates of up to 99%.…”
Section: Introductionmentioning
confidence: 99%